Observation of Microstructure Formation During Freeze-Drying of Dextrin Solution by in-situ X-ray Computed Tomography - Nakagawa, Kyuya; Tamiya, Shinri; Sakamoto, Shu; Do, Gabsoo; Kono, Shinji (Frontiers in Chemistry, 2018)
In-situ X-ray computed tomography (CT) was used to observe microstructure formations during freeze-drying of a dextrin solution. A specially designed freeze-drying stage was equipped at the X-ray CT stage. Frozen and dried microstructures were successfully observed. The CT images of the frozen solution clarified the ice crystal size increase and obvious boundary formation between the ice and freeze-concentrated phases upon performing post-freezing annealing at −5°C. These structural modifications emerged owing to Ostwald ripening and glassy phase relaxation. During the freeze-drying, pore microstructures formed as a consequence of water removal. The pores were replicas of the original ice microstructures; some pore microstructures newly formed by the removal of water. The latter mechanism was more obvious in the non-annealed sample than in the annealed sample. The glassy phase in the non-annealed solution was not perfectly freeze-concentrated; water was rapidly removed from this phase, losing its original microstructure. At this moment, the freeze-concentrated region piled up to new pore walls, which consequently thickened the pore walls. An image analysis estimated that the mean pore wall thicknesses for the non-annealed and annealed samples were 13.5 and 8.6 μm, respectively. It was suggested that the advantages of annealing are not only to reduce drying time owing to the modification of ice crystal morphologies but also to avoid quality loss related to the structural deformation of the glassy matters.